Kähler Yamabe minimizers on minimal ruled surfaces - Tønnesen-Friedman, Christina W. (MATHEMATICA SCANDINAVICA, 2002)
It is shown that if a minimal ruled surface P(E) → Σ admits a Kähler Yamabe minimizer, then this metric is generalized Kähler-Einstein and the holomorphic vector bundle E is quasi-stable.